Competitive advantages of intellectual property - Romanchyk, T. V.; Pererva, O. P. (Харківська державна наукова бібліотека імені В. Г. Короленка, 2024)
The report is devoted to the disclosure of the importance of intellectual property (IP) as an important tool for achieving competitive advantages in the modern business environment. The use of IP is a decisive factor influencing the development and implementation of innovative products and technologies, as well as the formation of a unique image of the company in the market. The report highlights that intellectual property not only protects businesses, but also opens up new opportunities for growth and development, making it an integral part of the modern competitiveness strategy.

Розкривається значення інтелектуальної власності як важливого інструмента для досягнення конкурентних переваг у сучасному бізнес-середовищі. Застосування ІВ є вирішальним фактором, що впливає на розвиток і впровадження інноваційних продуктів і технологій, а також на формування унікального іміджу компанії на ринку. Підкреслено, що інтелектуальна власність не лише захищає бізнес, але й відкриває нові можливості для зростання та розвитку, роблячи її невід’ємною частиною сучасної стратегії конкурентоспроможності.
Конкурентні переваги інтелектуальної власності
Keywords: intellectual property; competitive advantages; efficiency; legal protection; інтелектуальна власність; конкурентні переваги; ефективність; правовий захист